Diversifikasi Produk Kelompok Pengrajin Tenun Bima Berbasis Nano Teknologi di Kelurahan Rabadompu Timur Kota Bima - Agrippina Wiraningtyas; Wahyuni; Syarifuddin (Jurnal Pemberdayaan Masyarakat, 2022)
The problems faced by the Bima weaving craftsmen group, especially in East Rabadompu Village, Bima City, include a decrease in sales of Bima weaving products during the pandemic, which affected the income and welfare of Bima weaving craftsmen. So that this Community Partnership Program (PKM) aims to empower and increase the production of Bima weaving artisan groups in East Rabadompu Village, Bima City, by utilizing nanoparticle-based technology to make functional Bima weaving diversification products that are anti-bacterial and self-cleaning. The method used was training and mentoring in the manufacture and application of nanoparticles as a coating material and diversification of Bima weaving products. The results and impacts of the activity are Bima weaving diversification products in the form of pashminas, fans, and woven masks that are anti-bacterial and self-cleaning, with higher economic value. As well as increasing the knowledge and skills of activity participants so that they can apply nanotechnology and make woven diversification products. Therefore, it can increase the added value and economic value of woven products, so that it can also improve the welfare of Bima weaving craftsmen and MSME actors.